Structural Changes in the Arcuate Fasciculus and Recovery of Post-stroke Aphasia: A 6-Month Follow-up Study using Diffusion Tensor Imaging. (September 2022) - Bae, Cho Rong; Na, Yoonhye; Cho, Minjae; Hwang, Yu Mi; Tae, Woo-Suk; Pyun, Sung-Bom
Background: Temporal changes in the structural connectivity of major language tracts after stroke and their contribution to aphasia recovery are unclear. Objective: To investigate longitudinal arcuate fasciculus (AF) integrity changes and their relationship with post-stroke aphasia recovery using diffusion tensor imaging (DTI). Methods: Thirty-five patients with aphasia due to first-ever left hemispheric stroke underwent the Korean version of the Western Aphasia Battery and DTI at 1- and 6-month post stroke onset. Fractional anisotropy (FA), mean diffusivity (MD), radial diffusivity (RD), and axial diffusivity (AD) of both AF tracts were analyzed to evaluate the temporal changes in tract integrity and determine the correlation between changes (Δ; follow-up − initial) in DTI parameters and language scores. Results: At 6 months post-stroke, the mean FA decreased, and mean MD and RD increased in both hemispheres; however, compared with mean AD observed after 1 month, the mean observed at 6 months increased only in the left hemisphere ( P < .05). ΔFA of the left AF and proportional change in the aphasia quotient showed a significant positive correlation ( r = 0.365, P = .031). No correlation was found between changes in the right AF parameters and language score. The group with increased FA in the left AF showed more significant language improvement than the group with decreased FA. Conclusions: During the subacute stage, the integrity of AF decreased in both hemispheres in patients with aphasia, and the change in structural connectivity of the left AF was associated with language improvement.